Middle Jurassic volcanism in a magmatic-rich passive margin linked to the Caudiel Fault Zone (Iberian Range, East of Spain): biostratigraphical dating - Cortés, J.E.; Gómez, J.J. (Journal of Iberian Geology, 2016)
During the Early and Middle Jurassic, the Iberian Basin (East of Spain) recorded the transition from a generally magma-poor passive margin, which operated during the latest Triassic and most of Early Jurassic, to a magma-rich passive margin, developed from Pliensbachian to early Middle Jurassic. The mainly submarine pyroclastic volcanism, with minor lava flows, followed active NW and NE trending extensional fault zones. One of these zones of weakness, from which the volcanic deposits were expelled to the sea bottom, was the Caudiel Fault Zone. Two volcanic phases in relation to this weakness line over the Middle Jurassic times have been identified. The main phase occurred during the deposition of the El Pedregal Formation, and the other, less significant, is included between the Casinos and the El Pedregal formations. So far, the accurate age of these volcanisms, critical in the knowledge of the palaeogeographical and geodynamical evolution of the Iberian Basin, has remained uncertain. The ammonite content of the carbonate successions, with which these rocks are interbedded, allows precise biostratigraphical dating at the chronozone scale. For this purpose, 9 sections have been measured and 360 specimens of ammonites were collected and determined. The obtained data indicate that the Middle Jurassic volcanic deposits that are linked to the Caudiel Fault Zone and included into the El Pedregal Formation show a slight diachrony. They were deposited around the boundary between the Late Aalenian Concavum and the Early Bajocian Discites chronozones. However, in very restricted areas of the Caudiel Fault Zone, an older intra-Murchisonae volcanism was recorded.